Perbedaan Angka Kejadian Risiko Asfiksia Neonatorum Antara Bayi Kurang Bulan Dengan Bayi Cukup Bulan Pada Berat Bayi Lahir Rendah (Bblr) - Oktavionita, Vina; , Prof. Dr. Bambang Soebagyo, dr. Sp.A (K) (2017)
Background: Asphyxia becomes the third-leading cause of death in the world of infant mortality in the early period of life. Low birth weight infant (LBW) is one of the main causes that can cause birth asphyxia neonatorum. LBW infants with gestational age preterm and full-term become some risk factor of neonatal asphyxia. Objective: This study used observational analytic with cross sectional approach. It was using quota sampling technique, with 232 samples of low birth weight babies in 2015 and 2016 at the Hospital of Surakarta. Set data was obtained from medical records at the perinatal and then the Chi-Square Test is used to test of independence between two variables. Results: Chi-Square test is used for testing the differences of the incidence of neonatal asphyxia between preterm infants and term infants who have low birth weight. It generates P value = 0.292 which is over than 0.005. There are 27 asphyxia in preterm infants or equal to (11.6%) while there are only 23 term infants or equal to (9.6%). Conclusions: There was no significant difference of incidence of neonatal asphyxia between preterm infants and term infants who have low birth weight in Surakarta City Hospital.